2022
DOI: 10.3390/cancers14235905
|View full text |Cite
|
Sign up to set email alerts
|

Use of Selective Serotonin Reuptake Inhibitors Is Associated with a Lower Risk of Colorectal Cancer among People with Family History

Abstract: Individuals with a family history of colorectal cancer (CRC) are at a high risk of developing CRC. Preclinical and population-based evidence suggests that selective serotonin reuptake inhibitors (SSRIs) might play a role in preventing CRC. We performed a nationwide cohort study to explore whether the use of SSRIs could reduce CRC risk among individuals with family history. We identified individuals aged 50 and above who had one or more first-degree relatives diagnosed with CRC. A total of 38,617 incident SSRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“… 152 Population‐based cohort studies also revealed that there is a correlation between the utilisation of SSRIs and a potentially lower chances of developing CRC in people with a family history of this disease. 153 A recent evaluation and meta‐analysis of published observational studies unveiled that taking SSRIs was associated with decreased likelihood of developing HCC, with a dose‐dependent tendency. 154 SSRIs have also shown an association with a decreased risk of HCC and may lower the chances of HCC in patients with HBV in a dosage‐dependent fashion.…”
Section: Therapeutic Potential Of Serotonergic Pathway In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… 152 Population‐based cohort studies also revealed that there is a correlation between the utilisation of SSRIs and a potentially lower chances of developing CRC in people with a family history of this disease. 153 A recent evaluation and meta‐analysis of published observational studies unveiled that taking SSRIs was associated with decreased likelihood of developing HCC, with a dose‐dependent tendency. 154 SSRIs have also shown an association with a decreased risk of HCC and may lower the chances of HCC in patients with HBV in a dosage‐dependent fashion.…”
Section: Therapeutic Potential Of Serotonergic Pathway In Cancermentioning
confidence: 99%
“…An epidemiological study reported that the administration of SSRIs in patients with persistent clinical depression significantly decreased their likelihood of developing CRC 152 . Population‐based cohort studies also revealed that there is a correlation between the utilisation of SSRIs and a potentially lower chances of developing CRC in people with a family history of this disease 153 . A recent evaluation and meta‐analysis of published observational studies unveiled that taking SSRIs was associated with decreased likelihood of developing HCC, with a dose‐dependent tendency 154 .…”
Section: Therapeutic Potential Of Serotonergic Pathway In Cancermentioning
confidence: 99%
“…44 There is evidence that selective serotonin reuptake inhibitors (SSRI) reduce proliferation, leading to the death of tumor cells. 45…”
Section: Antipsychotic Agentsmentioning
confidence: 99%
“…They are generally considered to have fewer side effects and be less dangerous than older-generation antidepressants, such as tricyclic antidepressants, because they specifically target the serotonin transporter, rather than affecting a wide range of neurotransmitters (Wang et al, 2018). It was previously shown that drugs from the SSRI family exhibit anticancer properties (Nordenberg et al, 1999;Serafeim et al, 2003;Argov et al, 2009;Kast et al, 2013;Zhang et al, 2022). Moreover, it was suggested that SSRI members can be repositioned for cancer treatment (Peer and Margalit, 2006;Drinberg et al, 2014;Baú-Carneiro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%